2018
DOI: 10.1002/lary.27147
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term experience with intranasal bevacizumab therapy

Abstract: 4. Laryngoscope, 128:2237-2244, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
(79 reference statements)
2
17
1
1
Order By: Relevance
“…The findings of this study confirmed our previous results that RISBI is an effective treatment for HHT‐associated epistaxis . The improvement in QoL after RISBI strengthens this conclusion by adding a new dimension to the effectiveness of this treatment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings of this study confirmed our previous results that RISBI is an effective treatment for HHT‐associated epistaxis . The improvement in QoL after RISBI strengthens this conclusion by adding a new dimension to the effectiveness of this treatment.…”
Section: Discussionsupporting
confidence: 89%
“…The procedure is based on the vascular anatomy of the nose, and has been described in detail previously . Briefly, four intranasal sites are injected with 25 mg/ ml of bevacizumab on each side.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The findings were supported by Sadick et al in 2005, who also reported elevated levels of VEGF in addition to TGF-β1 in 31 HHT patients. 13 Later on, VEGF inhibitors were shown to efficiently treat many HHT patients, 15,25 strengthening the assumption that VEGF is an important mediator in this disease. In our study, however, the higher levels of VEGF and TGF-β1 in the patient group were not statistically significant.…”
Section: E46mentioning
confidence: 99%
“…12,13 A monoclonal antibody that binds and inhibits VEGF, bevacizumab, has been applied in clinical practice in treating HHT patients. 14 However, some HHT patients have limited or no response to bevacizumab, [15][16][17] and the pathogenesis of this highly heterogeneous disorder is complex and not yet fully determined, most probably involving other mediators than VEGF and members of the TGF-β superfamily.…”
Section: Introductionmentioning
confidence: 99%